Interaction between the Teaching/Learning of Formal Logic, Algorithms, Mathematics and French in a Multilingual and Multiethnic Context: Case of Mahajanga High School (Journal of Natural Language and Linguistics, 2024)
This article aims to study the eventual links between the teaching/learning of French, formal logic, mathematics and algorithms in a plurilingual and pluriethnic context, case of the secondary school of Mahajanga. The study will be based on surveys of the languages, and dialects spoken by pupils in class and their respective scores in French, formal logic, mathematics and algorithms. The data obtained will be further analysed using Implicative Statistical Analysis (ISA) under ICHC-MGK. Among the results of the ICHC-MGK analysis: students with a very strong level in logic are generally those who have a strong level in French, an average level in French generally leads to an average level in logic, those who are very strong in mathematics often have high skills in logic as well, students who are blamed in algorithms tend to be also blamed in logic, students who are strong in mathematics are probably also strong in algorithms and students with a very strong level in algorithms are generally those who express themselves in French. These results encourage us to consider future collaboration with French teachers in order to integrate logic into the teaching of French, to improve students’ levels in logic, mathematics and algorithms.